Revitalizing Family Functions in Efforts to Prevent Children Violence in North Aceh - Iromi Ilham; Abdullah Akhyar Nasution; Richa Meliza; Dinda Rosaleha; Ragil Nur Rahmalia (LPPM Universitas Malikussaleh, 2022)
North Aceh Regency is the region with the highest number of cases of child violence in Aceh Province. Of course, there are many factors behind it, one of which is the existence of a family that has not functioned optimally. This study examines how efforts to revitalize the functioning of family institutions to prevent violence against children. The research, which took place in North Aceh Regency, used a qualitative approach with observational data collection techniques, in-depth interviews, and document studies. Key informants in the study were stakeholders in the North Aceh Social Service, traditional leaders, religious leaders, and the general public. The data was analyzed using an interactive analysis model, namely: data reduction, data display, and conclusion affirmation. The results of the study found that the forms and types of violence against children that occurred in families in North Aceh were: a) physical violence; b) neglect; c) psychic violence; and 4) sexual violence. It's caused by factors of parental background and education level, family economic factors, and parental divorce. One form of social intervention that can be carried out to minimize cases of violence in the family is to restore the function of the family as the first madrasa and a shield of protection for the child. Therefore, the socialization of family functions should be improved with the main targets being families of young couples and families with a low level of education.